Semen traits, testicular morphometry and histopathology of cadmium-exposed rabbit bucks administered methanolic extract of Phoenix dactylifera fruit - Ansa, Anietie Archibong; Akpere, Odamesan; Imasuen, James Atekha (Acta Scientiarum. Animal Sciences, 2017)
This study evaluated the effect of Cd on some male reproductive parameters; and explored the therapeutic potentials of methanolic extract of Phoenix dactylifera (MEPD) fruit in averting such reproductive damages. 45 rabbit bucks aged 24-28 weeks and weighing 1.41-1.43 kg was used. The rabbits were assigned to 5 treatment groups (control, Cd-only, Cd + 300 mg MEPD, Cd + 600 mg MEPD and Cd + 900 mg MEPD) in a completely randomized design. The rabbits were dosed with 3 mg CdCl2 kg-1feed for 7 days followed by MEPD for 56 days after every 72 hours. Result of semen evaluation indicates that semen volume, motility, libido, concentration, total ejaculate, viability and morphology were significantly reduced by Cd compared to the normal control group. Testis density and epididymis length of the control rabbits were significantly different from the Cd-only exposed rabbits. Histopathological examination revealed severe testicular damage due to Cd. Indeed, treatment with MEPD significantly reversed the deleterious reproductive effects caused by Cd. In conclusion, cadmium drastically affected the testis of rabbits and treatment with MEPD alleviated some deleterious effects.